36
$\begingroup$

I have a couple of questions about tensor products:

Why is $\text{Hom}(V,W)$ the same thing as $V^* \otimes W$?

Why is an element of $V^{*\otimes m}\otimes V^{\otimes n}$ the same thing as a multilinear map $V^m \to V^{\otimes n}$?

What is the general formulation of this principle?

$\endgroup$
30
$\begingroup$

The result is generally wrong for infinite-dimensional spaces: see this question.

For finite dimensional space $V$, let's build an isomorphism $f : V^* \otimes W \to \hom(V,W)$ by defining

$$f(\phi \otimes w)(v) = \phi(v) w$$

This clearly defines a linear map $V^* \otimes W \to \hom(V,W)$ (it's bilinear in $V^* \times W$). Reciprocally, take a basis $(e_i)$ of $V$, then define $g : \hom(V,W) \to V^* \otimes W$ by:

$$g(u) = \sum_i e_i^* \otimes u(e_i)$$

Where $(e_i^*)$ is the dual basis to $(e_i)$ (I will use a few of its properties in $\color{red}{red}$ below). This is well-defined because $V$ is finite-dimensional (the sum is finite). Let's check that $f$ and $g$ are inverse to each other:

  • For $u : V \to W$, $$f(g(u))(v) = \sum e_i^*(v) u(e_i) = u \left( \sum e_i^*(v) e_i \right) \color{red}{=} u(v)$$ and so $f(g(u)) = u$.

  • For $\phi \otimes w \in V^* \otimes W$, $$g(f(\phi \otimes w)) = \sum e_i^* \otimes f(\phi \otimes w)(e_i) = \sum e_i^* \otimes \phi(e_i) w = \sum \phi(e_i) e_i^* \otimes w \color{red}{=} \phi \otimes w$$

And so $f$ and $g$ are isomorphisms, inverse to each other.


It is known that for finite dimensional $V$, then $(V^*)^{\otimes m} = (V^{\otimes m})^*$. Then an element of $V^{* \otimes m} \otimes V^{\otimes n}$ is an element of $(V^{\otimes m})^* \otimes V^{\otimes n} = \hom(V^{\otimes m}, V^{\otimes n})$. So by definition / universal property of the tensor product, it's a multilinear map $V^m \to V^{\otimes n}$.

$\endgroup$
  • $\begingroup$ That's great! I think another way to see that they are the same is as follows: given a basis $\{w_i\}$ for $W$, one can specify a linear transformation by picking any $n$ elements of $V^*$, and writing $$Tu = \varphi_1(u)w_1 + \dotsb + \varphi_n(u)w_n.$$ This is a bilinear map from $V^*\times W$ to $\text{Hom}(V,W)$, and it has "basis" $u_i^* \otimes w_j, \, 1\leq i\leq n, \, 1\leq j \leq m$. Note that $\varphi_i = \rho_i \circ T$, where $\rho_i$ is the projection onto the $i$th basis vector in $W$. $\endgroup$ – Eric Auld Feb 22 '14 at 23:41
  • 4
    $\begingroup$ I will also add that the general principle is that there is an embedding $$\theta: \text{Hom}(A, A')\otimes \text{Hom}(B,B') \hookrightarrow \text{Hom}(A\otimes B , A'\otimes B'),$$ which is an isomorphism if the spaces are finite-dimensional. This particular correspondence comes from letting $U=A,\,U'=\mathbb{F},\,B=\mathbb{F},\,B'=W.$ $\endgroup$ – Eric Auld Apr 22 '14 at 16:40

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.